The Influence of Sharia Financial Literacy and Trust in Customer Decisions with Religiosity as a Moderating Variable in Online Loan Applications in South Jakarta - Namira, Annisa; Nurlaila, Nurlaila; Arif Lubis, Fauzi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
The study explains the effect of Sharia financial literacy and trust on customer decisions with the aspect of religiosity in online loan applications in South Jakarta. The study uses multiple regression analysis with 2 variables (X), 1 variable (Z), and 1 variable (Y). This research was conducted to determine the partial and simultaneous effects of each variable (Sharia financial literacy and trust). The results indicate that the Sharia financial literacy variable does not have a significant effect on customer decisions. The trust variable has an effect on decisions, the religiosity variable has an effect on decisions, and the Sharia Financial Literacy variable does not affect the Religiosity variable as a moderating variable for decisions.